Effects of electric paravertebral muscle relaxation processes in the athletes heart - Syshko D. V. (Kharkov National Pedagogical University, 2013)
Influence of paravertebrals miorelaxation on electric processes in a heart at sportsmen is studied. Paravertebrals miorelaxation was the complex of exercises in a water environment directed on the decline of tone of paravertebral muscles. Before and after it was used of paravertebrals miorelaxation registered the indexes of electrocardiography at the sportsmen engaged in the Greek-Roman fight (n=22) by football (n=24) and heavy athletics (n=25). It is got, that at the sportsmen of engaged in the Greek -Roman fight after paravertebrals miorelaxation QRS and QT were it was increased, and R-R and PQ went down. At the sportsmen of engaged in heavy athletics HR and PQ went down after paravertebrals miorelaxation, R-R, QRS and QT were it was increased. At the sportsmen of getting busy by football the PQ interval shortened, and QRS and QT has multiplied. Findings testify to the presence of different mechanisms of adaptation of the conducting system of heart in the conditions of influencing of paravertebrals miorelaxation. These distinctions are fated by two basic factors: by the functional being of the cardio-vessels system on the whole and functional being of sine knot and conducting system of heart in particular.